Upregulation of PRMT6 by LPS suppresses Klotho expression through interaction with NF‐κB in glomerular mesangial cells - Tsai, Kuen‐Daw; Lee, Wen‐Xi; Chen, Wei; Chen, Bo‐Yu; Chen, Kuan‐Lin; Hsiao, Tzu‐Chia; Wang, Sue‐Hong; Lee, Yi‐Ju; Liang, Shan‐Yuan; Shieh, Jia‐Ching; Lin, Ting‐Hui (Journal of cellular biochemistry, 2018)
Lipopolysaccharide (LPS) released from gram‐negative bacteria stimulates immune responses in infected cells. Epigenetic modifications such as DNA methylation and protein methylation modulate LPS‐induced innate immune gene expressions. Expression of the Klotho protein decreased with LPS treatment in rats. In a cellular model, information regarding the effect of LPS on Klotho expression was meager. In the present study, we demonstrated that LPS triggered global DNA and protein methylation in glomerular mesangial MES‐13 cells. LPS upregulated protein expressions of enzymes central to cellular methylation reactions, especially protein arginine methyltransferase 6 (PRMT6) in MES‐13 cells. Expression of the Klotho protein was diminished by LPS and was restored by 5‐Aza‐2′‐deoxycytidine (5‐Aza‐2′‐dc), AMI‐1, and ammonium pyrrolidinedithiocarbamate (PDTC), but not adenosine aldehyde (AdOx). NF‐κB was identified as a substrate for arginine methylation and interacted with PRMT6 in MES‐13 cells. Inhibition of PRMT activity by AMI‐1 blocked LPS‐induced NF‐κB nuclear translocation in MES‐13 cells. Our data indicate that NF‐κB negatively regulated Klotho expression with an interaction with PRMT6, which was upregulated by LPS in MES‐13 cells. We show here the first time that protein arginine methyation is involved in the downregulation of Klotho expression by LPS. NF‐κB negatively regulated Klotho expression with an interaction with PRMT6, which was upregulated by LPS in MES‐13 cells. The specific arginine methyltransferase inhibitor, AMI‐1, restored Klotho expression suppressed by LPS, may have therapeutic value in treating renal inflammatory disorders and aging‐related diseases.